2013
DOI: 10.1108/jiabr-07-2012-0044
|View full text |Cite
|
Sign up to set email alerts
|

Islamic banking and economic growth in GCC & East Asia countries

Abstract: Purpose -The purpose of this paper is to assess the contribution of Islamic finance to economic growth in countries that were early adopters of Islamic banking: Malaysia, Indonesia and the Gulf Cooperation Council (GCC) countries. Design/methodology/approach -Through panel cointegration analysis, variance decompositions (VDCs) and impulse response functions, this study investigates the Islamic finance and growth nexus. Findings -Islamic banking is found to contribute to economic growth both in the long run and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 50 publications
2
31
0
4
Order By: Relevance
“…This study revealed that Islamic bank has positive impact on Indonesian economics growth. The study's results agree with the studies of Atici (2018), Hachicha and Ben Amar (2015), Mohd. Yusof and Bahlous (2013), and Rafay and Farid (2017) who reveal that Islamic banks positively affect the economic growth in long-run, however, in the short-run the impact is insignificant.…”
Section: Discussionsupporting
confidence: 89%
“…This study revealed that Islamic bank has positive impact on Indonesian economics growth. The study's results agree with the studies of Atici (2018), Hachicha and Ben Amar (2015), Mohd. Yusof and Bahlous (2013), and Rafay and Farid (2017) who reveal that Islamic banks positively affect the economic growth in long-run, however, in the short-run the impact is insignificant.…”
Section: Discussionsupporting
confidence: 89%
“…Just like Conventional Banks, Islamic banks function as intermediaries for channeling and there is a deficit saving sector to encourage activities in the economic sector. The difference is that the financial instrument is interest-free and runs according to Islamic law (Mohd. Yusof & Bahlous, 2013) Islamic finance can play an important role in encouraging economic growth in Indonesia, namely by financing the real sectors.…”
Section: ________________________________________________________________________________________________________________________________mentioning
confidence: 99%
“…Limited studies on Islamic banking development includes; Abduh and Omar (2012), Abduh and Chowdhury (2012), Boukhatem and Moussa (2018), Farahani and Dastan (2013), Furqani and Mulyany (2012), Kassim (2016), Manap et al (2012), Tabash and Anagreh (2017) and Yusof and Bahlous (2013) which established a positive impact. Boukhatem and Moussa (2018) further stated that the institutional framework of IB should be well developed for this impact to be more significant.…”
Section: Literature Reviewmentioning
confidence: 99%